Analisis Kualitas Daya Beban 1-Fasa Non-Linear Pada Computer Assisted Test CPNS - Masramdhani Saputra; Asfari Hariz Santoso; Saddani Djulihenanto; Gumilang, Binar Surya Gumilang (Politeknik Negeri Malang, 2023)
Along with technological advances in the digital era like today, which is growing faster, it has an impact on many fields. One field that has used a lot of technological developments is the CPNS Test which is based on the CAT (Computer Assisted Test) and uses many a lot of laptop/computer devices to support the implementation of the test. The many uses of computers, especially during the recruitment test, influence the quality of electrical power due to the typical character of the PC/laptop load, which is a non-linear single-phase load which results in neutral currents or currents containing harmonics. This is because the load on the pc/laptop has electronic components such as semiconductors where there is a switching process that creates an impure sinusoidal wave that causes harmonics. In the case study, the implementation of the CPNS CAT with the use of PC/laptop devices will certainly cause a fairly high THD and affect the electric current/power source. The thing that needs to be considered with a high THD and the supply of electricity from the generator is the effect on the performance of the generator and the influence of the generator’s lifetime. Briefly, the loading of the data is to reduce the derating generator set by 6,717 kVa so that the safe loading is 23.28 kVa with a maximum capacity of 30 kVa generator. Synchronous generator loading is recommended at 81% of its nominal value with a current THD of 50%.